2008
DOI: 10.2967/jnumed.108.053819
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Measures of Left Ventricular Function from Electrocardiographically Gated 82Rb PET with Contrast-Enhanced CT Ventriculography: A Hybrid PET/CT Analysis

Abstract: Because of the ultrashort tracer half-life and high positron energy of 82 Rb, PET images acquired with this tracer are noisier and of lower resolution than those obtained with other PET tracers. The validity of electrocardiographic gating using 82 Rb for assessment of left ventricular (LV) function is not well established. To support feasibility, we compared functional parameters from gated 82 Rb PET with simultaneous high-resolution contrastenhanced CT ventriculography, obtained as a byproduct a CT coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…This limitation makes quantification of functional parameters a bigger challenge than when using SPECT or gated PET with other tracers. Nevertheless, reproducibility of the software algorithms was good in our analysis, and the validity of gated 82 Rb PET results was recently demonstrated by us in a comparison with contrast-enhanced CT ventriculography (11). This prior study agreed well with the reference technique but also showed a systematic underestimation of LVEF by PET.…”
Section: Discussionsupporting
confidence: 72%
“…This limitation makes quantification of functional parameters a bigger challenge than when using SPECT or gated PET with other tracers. Nevertheless, reproducibility of the software algorithms was good in our analysis, and the validity of gated 82 Rb PET results was recently demonstrated by us in a comparison with contrast-enhanced CT ventriculography (11). This prior study agreed well with the reference technique but also showed a systematic underestimation of LVEF by PET.…”
Section: Discussionsupporting
confidence: 72%
“…Endocardial contours were identified on gated PET to determine left ventricular volumes and left ventricular ejection fraction, using previously validated commercially available software (CardIQ physio; GE Healthcare) (14). Quantification of MBF and MFR.…”
Section: Pet Image Analysismentioning
confidence: 99%
“…This showed great advantages: the scanning speed was fast, easy, safe, noninvasive, and of low cost; synchronism was good, in which image data of the coronary artery could be obtained and cardiac function determined in one-stop access, without examination interval, where cardiac function could reflect the current vein stenosis. We also found that there were some deficiencies: the time and spatial resolutions needed to be further improved, and there were still partial motion artifacts, which could affect the precise definition of left ventricular systolic end and diastolic end; and breathing exercises, rapid heart rate, heart rate arrhythmia, and severe coronary calcification would all affect coronary stenosis assessment (Ruixing et al, 2007;Chander et al, 2008). In addition, whether the use of metoprolol and contrast agents and saline in the contrast could affect left ventricular function still remains to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…It could cause heart expansion (left atrium and left ventricle), mainly due to myocardial ischemia, myocardial cell edema, interstitial hyperplasia and left ventricular remodeling, resulting in a decrease in left ventricular compliance and cardiac function. As the degree of stenosis increases, MM will increase, suggesting that left ventricular MM could be used as an effective indicator to determine left ventricular dysfunction, especially valuable for those patients with normal early LVEF values and no effects on general activities, and in whom MM is relatively stable in a certain period, with strong repeatability (Chander et al, 2008;Wang et al, 2009a;Krim et al, 2011).…”
Section: Discussionmentioning
confidence: 99%